Pengelolaan Limbah Medis Padat B3 Di Rumah Sakit Harapan Dan Doa Kota Bengkulu Tahun 2022: Evaluation of The Implementation Of Hazardous Waste Management At Harapan dan Doa Hospital in Bengkulu City - Kurniawan, Dony Kurniawan; Ramon, Agus; M.Amin; Wati, Nopia (Jurnal Ilmiah Mahasiswa Miracle, 2022)
Based on Minister of Health Regulation Number 07 of 2019 concerning Hospital Environmental Health, every health service facility must manage its environment in accordance with applicable regulations. This study aims to examine the management system for handling hazardous waste at Harapan Dan Doa Hospital, Bengkulu City. This research is a qualitative research with a descriptive approach that describes the state of the object under study. The data collection used is by interview and observation with interview guidelines and observation sheets. The informants in this study were 3 people, namely room nurses, Kesling officers and cleaning services and 1 triangulation informant, namely the head of the Igd Room at RSHD Bengkulu City. This research was conducted from March 24 to April 3, 2022 at Harapan and Doa Hospital, Bengkulu City. The results of the research at the Harapan and Doa Hospital in Bengkulu City showed that there were 3 stages at the Harapan and Doa Hospital in Bengkulu City that were not appropriate from the 9 stages according to the Minister of Health RI No. 07 of 2019 namely no identification of waste, no re-separation of waste at TPS, There is no waste treatment process. For this reason, it is hoped that the Harapan and Doa Hospital of Bengkulu City can improve the SOP for handling B3 waste in accordance with the Regulation of the Minister of Health of the Republic of Indonesia No. 07 of 2019 to improve performance and environmental health at Harapan and Doa Hospital Bengkulu City